Corruption in public procurement: entrepreneurial coalition building. - Hudon, Pierre-André; Garzón, César (Crime, Law & Social Change, 2016)
This article presents a comprehensive theoretical approach to the study of procurement corruption. It argues that corruption in public procurement can be explained by the creation and development of 'corrupt procurement coalitions' (CPCs). Functioning as a network built by corruption entrepreneurs seeking to 'milk' the procurement process, a CPC must accomplish three interrelated tasks to succeed: 1) identifying which members to include and organizing interactions of said members, 2) generating and redistributing benefits, and 3) evading internal and external control. CPCs are structured in an inner/peripheral configuration, where the inner network controls the core activities, and the peripheral networks can be activated at will when illegal tasks need to be externalized.